Machine learning in computer-aided diagnosis medical imaging intelligence and analysis - Suzuki, Kenji, 1968 Oct. 5-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book provides a comprehensive overview of machine learning research and technology in medical decision-making based on medical images"--Provided by publisher.
11. A model-driven bayesian method for polyp detection and false positive suppression in CT colonography computer-aided detection / Xujiong Ye and Greg Slabaugh -- 12. Computer-aided image analysis and detection of prostate cancer: using immunostaining for alpha-methylacyl-CoA racemase, p63, and high-molecular-weight cytokeratin / Yahui Peng, Yulei Jiang and Ximing J. Yang -- 13. Magnetic resonance image analysis for brain CAD systems with machine learning / Hidetaka Arimura ... [et al.] -- 14. CADrx for GBM brain tumors: predicting treatment response from changes in diffusion-weighted MRI / Jing Huo, Matthew S. Brown and Kazunori Okada -- 15. Autism diagnostics by 3D shape analysis of the corpus callosum / Ahmed Elnakib ... [et al.] -- 16. Neuroimage classification for early diagnosis of Alzheimer's disease / Yong Fan and Christos Davatzikos -- 17. Manifold learning for medical image registration, segmentation, and classification / Paul Aljabar, Robin Wolz and Daniel Rueckert -- 18. Learning manifolds: design analysis for medical applications / Diana Mateus ... [et al.] -- 19. Automatic organ localization on X-ray CT images by using ensemble-learning techniques / Xiangrong Zhou and Hiroshi Fujita -- 20. Applications of machine learning in real-time tumor localization / Ruijiang Li and Steve B. Jiang.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed December 19, 2011).
Keywords: Diagnostic imaging -- Digital techniques; Image analysis; Machine learning; Automated segmentation computed tomography scans; Clinical machine learning; Computer-aided detection and diagnosis; Content-based image retrieval; Ensemble learning; Fuzzy methods for image analysis; Machine learning techniques; Magnetic resonance imaging; Medical image registration, segmentation and classification; Relevance feedback; Electronic books